Women hicks. Two views on everybody in rural sao paulo - De Moraes Silva, Maria Aparecida; Medeiros De Melo, Beatriz; Abrao De Moraes, Lara [UNESP] (Presses Univ Mirail, 2012)
Based on researches undertaken among peasant families in two districts belonging to Sao Paulo's state - Santo Antonio da Alegria (in the state's North Eastern region), and Jales (in the North Western one) this article proposes to analyse the part played by women in domestic and trade production, in the preservation of material heritage (the land) and immaterial one (celebrations, memory and traditions). The methodology employed takes into consideration the qualitative data as well as direct observation. The obtained results, in addition to revealing women's visibility, show their importance in the construction of identitary bonds in the paulista rural world, taking into consideration its caipira past as well as its present situation.
Keywords: Peasants; Way of life; Moral economy; Resistance; Agriculture in Sao Paulo's state